2010
DOI: 10.1100/tsw.2010.44
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbitacin: Ancient Compound Shedding New Light on Cancer Treatment

Abstract: Cucurbitacins and their derivatives are triterpenoids found in medicinal plants known for their diverse pharmacological and biological activities, including anticancer effects, throughout human history. Although initial attention to cucurbitacin as a potential anticancer drug withered for decades, recent discoveries showing that cucurbitacin is a strong STAT3 (Signal Transducers and Activators of Transcription-3) inhibitor have reclaimed the attention of the drug industry one more time. There is increasing evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(120 citation statements)
references
References 30 publications
3
112
1
4
Order By: Relevance
“…32 Several reports have indicated the synergistic effect of cucurbitacin with known chemotherapeutic agents, such as doxorubicin and gemcitabine. 33 In the current study, our data revealed that treatment with cucurbitacin I in CD133-positive NSCLC cells effectively improved their chemoresistance to cisplatin, doxorubicin, 5-FU, and paclitaxel (Fig. 5).…”
Section: Discussionsupporting
confidence: 59%
“…32 Several reports have indicated the synergistic effect of cucurbitacin with known chemotherapeutic agents, such as doxorubicin and gemcitabine. 33 In the current study, our data revealed that treatment with cucurbitacin I in CD133-positive NSCLC cells effectively improved their chemoresistance to cisplatin, doxorubicin, 5-FU, and paclitaxel (Fig. 5).…”
Section: Discussionsupporting
confidence: 59%
“…The actin cytoskeletal reorganization is involved in these phenotypes, and several toxins targeting on the networks of actin filaments have been reported to efficiently inhibit cell cycle progression and induce apoptosis in cancer cells [74,75]. For instance, cucurbitacins [76,77] derived from medicinal plants have many isoforms and they are widely used in cancer therapy because they disrupt the formation of filamentous actin and subsequently cause G2/M phase arrest and apoptosis in breast cancers [78], glioblastoma (GBM) [79], and prostate cancer [80]. In addition, a series of actin toxins that display highly antitumor effects have been used for anticancer researches by interfering the actin polymerization and depolymerization.…”
Section: Adf/cofilin In Cancer Growth and Metastasismentioning
confidence: 99%
“…However, at high concentrations, where growth of cells is inhibited, the cucurbitacins would be cytotoxic (Lee et al, 2010). The observation in this study, where cucurbitacins were undetectable (Figures 2 and 3), is important for the potential commercialisation of Nemarioc-AL and Nemafric-BL phytonematicides.…”
Section: Resultsmentioning
confidence: 61%
“…In density-dependent growth (DDG) context , the accumulation of cucurbitacin in edible produce and in subsequent products would be risky since in small quantities that characterise chemical residues, cucurbitacins could stimulate cell division in animals, thereby inducing cancer (Lee et al, 2010). However, at high concentrations, where growth of cells is inhibited, the cucurbitacins would be cytotoxic (Lee et al, 2010).…”
Section: Resultsmentioning
confidence: 99%